Causal order in parallel and distributed simulation systems - Zeng, Yi (2008)
The causal order captures the most basic and important event ordering in distributed systems. In our research, it is applied to solve major problems in two categories of parallel and distributed simulation (PADS) applications, i.e., consistency in distributed virtual environments (DVEs) and performance in Time Warp simulation.